Reconstructing Fractional Holographic Dark Energy with scalar and gauge fields - Ayush Bidlan; Paulo Moniz; Oem Trivedi (European Physical Journal C: Particles and Fields)
Abstract We revisit the Fractional Holographic Dark Energy (FHDE) model to reconstruct it by means of dynamic candidates such as (i) Quintessence, (ii) K-essence, (iii) Dilaton, (iv) Yang–Mills condensate, (v) DBI-essence, and (vi) Tachyonic fields in a flat Friedmann–Robertson–Walker (FRW) Universe. In particular, the dark-energy possibilities (i)–(vi) are formulated through suitable field descriptions. Being concrete, we establish a comprehensive correspondence between FHDE and suitable scalar and gauge field frameworks that co-substantiate our investigation and subsequent discussion. In more detail, we methodically compute the corresponding Equation of State (EoS) parameters and field (kinetic and potential) features for the fractional parameter ( $$α $$ α ) range, viz. $$1<α \le 2$$ 1 < α ≤ 2 . Conclusively, our results show that the modifications brought by the fractional features satisfactorily enable late-time cosmic acceleration, together with avoiding quantum instabilities by preventing the EoS from entering the phantom divide i.e., $$ω (z)→ -∞ $$ ω ( z ) → - ∞ , which is a common issue in standard scalar field models without fractional dynamics (e.g., K-essence field). Our findings further indicate that fractional calculus attributes can be significant in addressing the challenges of dark-energy models by offering a robust framework to prospect late-time acceleration and properly fitting observational constraints. Notably, we find that as the fractional features start to dominate, the EoS parameter of all the effective field configurations asymptotically approaches a $$\varLambda $$ Λ CDM behaviour in the far-future limit $$z→ -\,1$$ z → - 1 . In summary, the recent perspective introduced by FHDE can indeed be cast as a promising aspirant through the use of prominent field frameworks.